Towards Inclusive Translation Technology : Perceptions and Practices of Accessibility among Translation Technology Developers - Stanger, Jennifer (My University, 2024)
This study investigated the perceptions and implementation strategies regarding accessibility among professionals engaged in translation technology development. It addressed three key inquiries: 1. How do translation technology developers perceive accessibility within the broader context of technology development and specifically within translation technology? 2. What strategies do these developers employ to integrate accessibility in their technologies? 3. What organisational practices characterise translation technology development? Data were collected through an online survey questionnaire featuring both closed and open-ended questions. The questionnaire was structured into three thematic sections, exploring perceptions of accessibility in technology development generally, within the realm of translation technology, and strategies for implementation along with organisational practices. Employing a mixed-method approach, the study utilised quantitative and qualitative techniques, with findings contextualised against prior research on web and translation technology accessibility. The results indicated that translation technology developers acknowledge the significance of accessibility, extending beyond disability needs to enhance overall usability and user satisfaction. Developers use Various integration strategies which are mainly dependent on awareness of individual developers. Thus, a lack of organisational practices is noted, with respondents expressing a strong desire for enhanced collaboration, particularly with end-users. These findings align with recent accessibility initiatives undertaken by translation technology companies, anticipating a more promising landscape for accessible translation technology.
Keywords: translation technology, accessibility, inclusivity, usability, design for all